The Detection of Fraudulent Financial Statement with Fraud Diamond Analysis - Arfiyadi, Arfiyadi; Anisykurlillah, Indah (Accounting Analysis Journal, 2016)
The purpose of this study was to analyze the prediction of fraudulent financial statement by fraud diamond. The independent variables of this research are of financial stability, external pressure, financial target, nature of industry, ineffective monitoring, rationalization, and capability. The population of this research are 93 companies in LQ-45 listed in Indonesia Stock Exchange during the period 2010-2015. Data were selected by purposive sample, it obtained 18 companies with 92 unit analysis firms for sample of the research. Logistic Regression analysis techniques was used to analyze data, and it was helped by IBM SPSS 21 software. The findings show that nature of industry, and rationalization have positive significant impact toward fraudulent financial statements. While the financial stability, external pressure, financial target, ineffective monitoring, and capability didnât have significant impact toward fraudulent financial statements.